2007
DOI: 10.1177/0310057x0703500406
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Anticoagulant Effect of Low-Dose Subcutaneous Unfractionated Heparin as Determined Using Thrombelastography

Abstract: In an observational study using heparinase-modified thrombelastography, we investigated the percentage of elective cardiothoracic surgical patients receiving low-dose unfractionated heparin (5000 IU 12 hourly subcutaneously) who had a demonstrable systemic heparin effect. Blood samples were obtained at induction from 40 adult elective cardiothoracic surgical patients who had received 5000 IU unfractionated heparin subcutaneously within six hours. Simultaneous kaolin and heparinase-modified thrombelastographie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…9 Although both studies used small study populations, and larger studies are needed adequately to assess the effect of thromboprophylaxis on venous thromboembolism post CS, it seems likely that UH at this dose has an insufficient anticoagulant effect for clinical use and should be abandoned. TEG can, however, detect a heparin effect, 11,12,15,17 and the current findings suggest that it can do so when anti-factor Xa assays cannot.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…9 Although both studies used small study populations, and larger studies are needed adequately to assess the effect of thromboprophylaxis on venous thromboembolism post CS, it seems likely that UH at this dose has an insufficient anticoagulant effect for clinical use and should be abandoned. TEG can, however, detect a heparin effect, 11,12,15,17 and the current findings suggest that it can do so when anti-factor Xa assays cannot.…”
Section: Discussionmentioning
confidence: 54%
“…19 A heparin effect has been arbitrarily defined as a difference >25% between plain and heparinise R time samples. 15 Nine patients showed this effect, yet the majority remained hypercoagulable compared to baseline results. Only two samples (in patients 4 and 14 at 4 h) were hypocoagulable following heparin relative to their baseline sample, and in neither of these was the difference >25%.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Conversely, Boyce et al. recently demonstrated a significantly shorter R time, shorter K time and wider alpha angle following caesarean section compared with pre‐operative values [18]. However, the greatest increase in coagulability in their study was found at 3 h. Since our postoperative samples were taken either immediately postoperatively, or 4 h following enoxaparin administration (itself given 3–4 h following surgery), we may have missed the peak hypercoagulable period.…”
Section: Discussionmentioning
confidence: 75%
“…A heparin effect has been defined as a TEG R time > 25% longer than the heparinase‐corrected control [18, 19]. Of the 33 patients who had post‐enoxaparin TEG samples, only 17 (52%) showed this effect, although 24 (73%) were hypocoagulable compared to their pre‐operative samples, with increased R times, decreased MA and decreased CI values.…”
Section: Discussionmentioning
confidence: 99%